2022
DOI: 10.1093/nar/gkac991
|View full text |Cite
|
Sign up to set email alerts
|

A forward genetic screen in C. elegans identifies conserved residues of spliceosomal proteins PRP8 and SNRNP200/BRR2 with a role in maintaining 5′ splice site identity

Abstract: The spliceosome undergoes extensive rearrangements as it assembles onto precursor messenger RNAs. In the earliest assembly step, U1snRNA identifies the 5′ splice site. However, U1snRNA leaves the spliceosome relatively early in assembly, and 5′ splice site identity is subsequently maintained through interactions with U6snRNA, protein factor PRP8, and other components during the rearrangements that build the catalytic site. Using a forward genetic screen in Caenorhabditis elegans, we have identified suppressors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Importantly, splicing is detected at the wt splice site, even though that intron now begins with UU. Usage of the +23 and -1 cryptic sites lead to out of frame messages, and we found identified extragenic suppressors that increase the relative usage of the wt splice site (even though the mutant intron begins with UU), lead to improved locomotion (Roller et al 2000;Dassah et al 2009;Mayerle et al 2019;Cartwright-Acar et al 2022;Suzuki et al 2022). Even though use of the +23 and -1 cryptic sites lead to messages that are out of frame, transcripts that use these sites are not subject to nonsense-mediated decay.…”
Section: Generating New Snu-66 H765 Mutantsmentioning
confidence: 81%
See 1 more Smart Citation
“…Importantly, splicing is detected at the wt splice site, even though that intron now begins with UU. Usage of the +23 and -1 cryptic sites lead to out of frame messages, and we found identified extragenic suppressors that increase the relative usage of the wt splice site (even though the mutant intron begins with UU), lead to improved locomotion (Roller et al 2000;Dassah et al 2009;Mayerle et al 2019;Cartwright-Acar et al 2022;Suzuki et al 2022). Even though use of the +23 and -1 cryptic sites lead to messages that are out of frame, transcripts that use these sites are not subject to nonsense-mediated decay.…”
Section: Generating New Snu-66 H765 Mutantsmentioning
confidence: 81%
“…These results indicate that snu-66(H765G) is indeed a locomotion defect suppressor of unc-73(e936) at the level of splicing, phenocopying the mutation in its interacting partner residue snrp-27(M141T). Given that so many of the suppressor alleles have been dominant, we have yet to saturate the unc-73(e936) suppressor screen (Cartwright-Acar et al 2022). Therefore, it is satisfying that a specific point mutation at a position identified as a SNRP-27(M141T)-interacting residue in cryoEM studies is a previously undiscovered unc-73(e936) suppressor.…”
Section: Generating New Snu-66 H765 Mutantsmentioning
confidence: 99%
“…They found that the majority of alternative 5’SS usage changes were in introns containing true alternative 5’SS and that suppressors rarely activated novel cryptic alternative 5’SS. They further RT-PCR verified several of the alternative 5’SS and 3’SS events, and finally asserted that the class II suppressors they studied may work at mutually exclusive stages of spliceosome assembly or use different mechanisms to maintain 5’SS identity based on their ability to differentiate between alternative 5’ splicing events that are unique to particular suppressors (63). Draper et al (2023) quantified events across polyribosome fractions and between primates to assess the conservation of alternative splicing coupled to translational control (ASTC).…”
Section: Discussionmentioning
confidence: 96%
“…Higher splicing efficiency and increased 5'-cryptic splice-site selection of a reporter gene, suggested a role for hBrr2 in maintaining 5'-splice site identity. A genetic screen in Caenorhabditis elegans has identified a strong suppressor of 5'SS mutation and cryptic splicing in the unstructured N-terminal region of Brr2 10 . Moreover, truncation of this region in yeast has resulted in the reduction of U6 and U5, and accumulation of U1 in the B act spliceosome 37 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of this key regulatory mechanism has not been elucidated in the human spliceosome and in human pre-mRNA splicing, so far. Fine-tuning of Brr2 activity by PRPF8 may play a role in splice site selection and maintaining optimal splice sites and splicing fidelity 9,10 and deciding alternative splicing events 11 . PRPF8 RP patient mutations, through dysregulation of hBrr2 by PRPF8, therefore provide a valuable opportunity to delineate regulatory mechanisms of hBrr2 on human splicing in health and disease.…”
mentioning
confidence: 99%